Evaluation of repulsive particle swarm method for phase equilibrium and phase stability problems - Rahman, Imran; Das, Anwesh Kr.; Mankar, Raju B.; Kulkarni, B. D. (Fluid Phase Equilibria, 2009)
Phase equilibrium and stability problems are of crucial importance in simulation, design and optimization of several separation processes. Recently, these problems have been solved using minimization of Gibbs free energy, using global optimization techniques. In this paper, repulsive particle swarm (RPS), a recent global optimization technique is explored for the Solution of phase stability and phase equilibrium. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid equilibria; Phase equilibrium; Phase stability analysis; Repulsive particle swarm method